2007
DOI: 10.1105/tpc.106.042911
|View full text |Cite
|
Sign up to set email alerts
|

Rice NON-YELLOW COLORING1 Is Involved in Light-Harvesting Complex II and Grana Degradation during Leaf Senescence

Abstract: Chlorophyll degradation is an aspect of leaf senescence, which is an active process to salvage nutrients from old tissues. non-yellow coloring1 (nyc1) is a rice (Oryza sativa) stay-green mutant in which chlorophyll degradation during senescence is impaired. Pigment analysis revealed that degradation of not only chlorophylls but also light-harvesting complex II (LHCII)-bound carotenoids was repressed in nyc1, in which most LHCII isoforms were selectively retained during senescence. Ultrastructural analysis of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
411
0
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 460 publications
(442 citation statements)
references
References 48 publications
20
411
0
11
Order By: Relevance
“…Hence, the gene mutations of type C mutants were considered to affect the pathway of chl breakdown directly. This has been confirmed and is obvious for pao1 and nyc1, which are affected in catabolic steps of the pathway (Pružinská et al, 2003;Pružinská et al, 2005;Kusaba et al, 2007). The situation is different for sgr/sid mutants, since so far the function of SGR/SID could not unequivocally be demonstrated.…”
Section: Introductionmentioning
confidence: 73%
“…Hence, the gene mutations of type C mutants were considered to affect the pathway of chl breakdown directly. This has been confirmed and is obvious for pao1 and nyc1, which are affected in catabolic steps of the pathway (Pružinská et al, 2003;Pružinská et al, 2005;Kusaba et al, 2007). The situation is different for sgr/sid mutants, since so far the function of SGR/SID could not unequivocally be demonstrated.…”
Section: Introductionmentioning
confidence: 73%
“…Genes encoding both enzymes have recently been identified Meguro et al 2011). In Arabidopsis and rice, Chl b reductase is encoded by two genes, NON-YELLOW COLOR-ING1 (NYC1) and NYC1-LIKE (NOL) (Horie et al 2009;Kusaba et al 2007;Sato et al 2009). NYC1 and NOL are members of the family of short-chain dehydrogenases/ reductases and share around 50 % sequence identity.…”
Section: Chlorophyll Catabolic Enzymesmentioning
confidence: 99%
“…1 d C1 stereochemistry refers to the type of pFCC, i.e. pFCC (1) or epi-pFCC (epi), formed in the respective species or genus; nd, not determined e Source of material used for catabolite isolation: E, in vitro enzymatic PAO/RCCR assays; F, fruits; L, leaves f In At-NCC-3, the site of hydroxylation is indicated to be C7 (rather than C8 2 ) g Hv-UCC-1 and Ap-UCC-1 are indicated to be pseudo-enantiomers (Müller et al 2011) b reductase, although Chl b reductase activity could so far not be demonstrated with recombinant NYC1 (Horie et al 2009;Kusaba et al 2007). A possible explanation is the hydrophobic nature of NYC1 proteins; they contain three predicted transmembrane spanning domains, fitting the proposed biochemical features of Chl b reductase.…”
Section: Chlorophyll Catabolic Enzymesmentioning
confidence: 99%
“…Chlorophyll b is reduced to 7-hydroxymethyl chlorophyll a by chlorophyll b reductase (CBR). Two CBR isozymes, NON-YELLOW COLORING 1 (NYC1) and NYC1-Like (NOL), are known in land plants (Kusaba et al 2007). An NYC1-deficient mutant cannot degrade LHCII, suggesting that chlorophyll b degradation triggers LHCII degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Although the phenotypes of CBR-deficient mutants during senescence have been studied (Kusaba et al 2007;Horie et al 2009;Sato et al 2009), the effect of the light conditions on the degradation activity of chlorophyll b has not yet been determined. In this report, we analyzed mutant plants that are defective in chlorophyll b degradation under a high-light treatment to elucidate the role of chlorophyll b degradation in the regulation of the light-harvesting system.…”
Section: Introductionmentioning
confidence: 99%